Comparison of Algebra Learning Using Motion Graphic Animation Media and Conventional Methods among Grade VII Junior High School Students - Deli; Jason Phang; Tony Wibowo (Universitas Pendidikan Ganesha, 2026)
Mathematics learning in algebra often faces challenges due to the abstract nature of the concepts, resulting in students' low conceptual understanding in conventional learning. This condition indicates the need for innovative learning media that can visualize concepts in a more concrete and engaging manner. This study aims to analyze the effectiveness of using motion graphic animation media in improving students' algebra learning outcomes. This study uses a quantitative approach with a control group experimental design involving an experimental group given treatment using animation media and a control group following conventional learning. The research subjects consisted of junior high school students selected as the research sample. Data collection was carried out through written tests given before and after the treatment to measure improvements in learning outcomes, with instruments that have undergone validity and reliability tests. Data were analyzed using inferential statistical techniques to test differences in learning outcomes between the two groups. The results show that the use of motion graphic animation media provides a more significant improvement in learning outcomes compared to conventional learning, as well as being able to deepen conceptual understanding and improve the distribution of student learning outcomes. Thus, motion graphic animation media is proven effective as an alternative innovative learning strategy. The implications of this research show that the integration of technology-based visual media can be a solution to overcome learning difficulties in abstract material and support the continuous improvement of the quality of mathematics learning.